Registro de la subfamilia Acaenitinae y de la especie Arotes pammae Gauld (Hymenoptera: ichneumonidae) para México. - Ruíz Cancino, Enrique; Kasparyan, Dmitri R. (Instituto de Ecología, A.C., 2008)
The subfamily Acaenitinae and the species Arotes pammae Gauld, 1991 are registered for Mexico for the first time, from material collected in the State of Veracruz.